CLINICAL EFFICACY OF THE CONVENTIONAL GLASS IONOMER CEMENT AND RESIN MODIFIED GLASS IONOMER CEMENT IN PRIMARY MOLARS - Mufti, Ayesha Sabeen (Journal of Ayub Medical College Abbottabad, 2014)
Background: Dental caries is the most prevalent communicable disease in the world amongst the population of the children. Objective: To compare the outcome of restorations in primary molars using two Glass ionomer cements Ketac-Molar, a Glass ionomer cement (GIC) and Vitremer, a Resin modified glass ionomer cement (RMGIC) in small and medium sized cavities. Methodology: A randomized controlled trial was conducted on 27 children between ages 4-9 years who had bilateral matched pair of carious lesions in primary posterior teeth. A split mouth design was used in which two materials, Ketac Molar and Vitremer, were placed on contralateral sides of the oral cavity in the same patient. The aim was to compare clinical performance of these restorations after 6 months using United States Public Health Service (USPHS) criteria. Data were collected six months after restoration using USPHS criteria. Statistical analysis was conducted using SPSS-16. Categorical variables were described as frequencies, and percentages. Chi-square test was used to compare the frequencies between groups keeping statistical significance at p‰¤0.05. Results: Based on the USPHS criteria, after six months the results of Ketac Molar and Vitemer were comparable, except for sensitivity where RMGIC performed significantly better (p=0.040). Though not significantly different, GIC performed better in 2/10 variables namely marginal discoloration and surface staining. RMGIC did better in 4/10 variables namely marginal integrity, retention, secondary caries and sensitivity. Both cements performed almost equally well in 4/10 variables, i.e., colour match, anatomic form, surface texture and proximal contact. Conclusion: Overall the clinical performance of Vitremer was better than Ketac molar and is to be considered as a preferable material for restoration of primary molars. More studies are recommended to confirm the results of the present study. Keywords: Dental caries, Restoration, Ketac Molar (Glass Ionomer Cement), Vitremer (Resin Modified Glass Ionomer Cement), USPHS criteria